2021
DOI: 10.3892/ol.2021.13023
|View full text |Cite
|
Sign up to set email alerts
|

circRNA circ_POLA2 increases microRNA‑31 methylation to promote endometrial cancer cell proliferation

Abstract: Circular RNA (circRNA) circ_POLA2 is an oncogene in lung and cervical cancers. However, the role of circ_POLA2 in other types of cancer is unknown. The present study investigated the role of circ_POLA2 in endometrial cancer (EC). The mRNA expression levels of circ_POLA2 and microRNA (miR)-31 in EC and paired adjacent normal tissues were analyzed using reverse transcription-quantitative (RT-qPCR). Overexpression of circ_POLA2 was achieved in the EC cell lines, and its effects on miR-31 mRNA expression level and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Cir_POLA2 has been reported as an oncogene of lung cancer. 19 It has been found that overexpression of Cir_POLA2 can promote the proliferation of acute myeloid leukemia cells. 20 Circ_POLA2 may upregulate the G protein subunit beta 1 (Notch pathway-related molecules) by serving as an endogenous competing RNA for miR-326.14.…”
Section: Discussionmentioning
confidence: 99%
“…Cir_POLA2 has been reported as an oncogene of lung cancer. 19 It has been found that overexpression of Cir_POLA2 can promote the proliferation of acute myeloid leukemia cells. 20 Circ_POLA2 may upregulate the G protein subunit beta 1 (Notch pathway-related molecules) by serving as an endogenous competing RNA for miR-326.14.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that LAMA4 could affect the level of Notch ligand and its receptor by regulating TGF-β1 [18], thereby inducing the expression of some key proteins related to the occurrence and development of HCC. Cir_POLA2 has been reported as an oncogene of lung cancer [19]. It has been found that overexpression of Cir_POLA2 can promote the proliferation of acute myeloid leukemia (AML) cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…Proliferation, invasion and metastasis are the basic features of malignant tumors, involving a series of complex multi-step interactions among tumor cells and the host (70). For example, bladder cancer, gastric cancer (47,48) and EC all have the potential of proliferation, invasion and metastasis (70,71).…”
Section: Circrnas Regulate Cell Proliferation and Motility In Ecmentioning
confidence: 99%
“…At present, several studies have demonstrated that circRNAs adsorb miRNAs through numerous pathways and fulfill a role in EC development (28,29,71). For example, circIFT80 [circBase ID (http://www.circbase.org/), hsa_circ_0067835], circWHSC1, circSLC6A6, circATP2C1 (circBase ID, hsa_circ_0005797) and circPOLA2 participate in the invasion, proliferation and metastasis of EC through the adsorption of miR-324-5p (71), miR-646 (28), miR-497-5p (29), miR-298 (30) and miR-31 (70), respectively. Notably, it has been reported that activation of these pathways depends on exogenous amino acids for energy (72).…”
Section: Circrnas Regulate Cell Proliferation and Motility In Ecmentioning
confidence: 99%